Three Rs for Middle Level Education: The 2022 NCPOMLE John VanHoose Lecture - David C Virtue (Middle Grades Review, 2023)
The author contends the most prominent challenges and conditions facing middle level education now and in the near future point to three imperatives for the field: middle level education must be relevant, resilient, and robust. After conceptualizing the field of middle level education as an interdisciplinary, applied field of study concerned with the formal education of young adolescent learners in school settings, the author discusses each of the three imperatives and provides recommendations for scholars to move forward alongside professionals in middle level schools and classrooms to achieve a bright educational future for young adolescents.
Keywords: educational research; middle grades reform& #x27; middle level education; teacher education